Artificial Intelligence Integration in Mobile Applications: Innovation and Challenges in Supporting Quran Memorization and Review - Khairulnazrin Nasir; Rahim Kamarul Zaman; Ahmad Bazli Ahmad Hilmi; Abdul Hakim Mahadzir; Ahmad Mukhlis bin Mustaffa (Centre of Quranic Research (CQR), University of Malaya, 2025)
Index Publication (Tier 2)